Disappropriation and Composting in Valeria Luiselli’s Lost Children Archive - Peinado-Abarrio, Rubén (Complutense Journal of English Studies, 2022)
This article offers first a review of Josefina Ludmer’s ‘postautonomy’, Cristina Rivera Garza’s ‘disappropriation’, and Verónica Gerber Bicecci’s ‘compost writing’ as useful categories for the analysis of recent works of fiction based on complexity and relationality. These three different but interrelated concepts are then applied to the study of Valeria Luiselli’s first novel in English, Lost Children Archive (2019), a fragmentary text that manages to convey a sense of interconnection through its multi-layered analysis of border policies, forced migration, and environmental justice. Particular emphasis is laid on Luiselli’s politics of quotation as developed in both textual and paratextual material; her archival method, which contributes to the polyphonic impetus of the novel and presents the archive as a tool for resistance, and the posthuman ethos that informs her work, advocating a nature-culture continuum in a constant movement towards a horizontal communication scheme.